Research on Marketing Strategy of Indonesian Tourism Facing Chinese Tourist Source Market 印尼旅游业面向中国客源市场的营销策略研究 - Chaoxia, SONG; Hua, ZHANG; Jia, YAN (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2023)
How to grasp the development opportunities brought by the Belt and Road Initiative and further expand China's tourist source market is an issue worthy of the attention of the Indonesian government. In tourism development, Indonesia should give priority to the promoting role of tourism development in the growth of economic aggregate, attach great importance to the marketing and promotion of Chinese tourist source market, and pay special attention to the large scale of Chinese tourist source market, large number of tourists and high level of expenditure, as well as the characteristics of outbound tourism consumption behavior featuring large number of independent tourists, long stay, emphasis on destination safety and tourism experience. In order to further expand the Chinese tourist market, price strategies, scenic strategies, information strategies and visa strategies can be targeted in tourism marketing promotion, so as to better promote the healthy development of Indonesian tourism and promote the sustainable growth of Indonesian national economy.